2008
DOI: 10.1007/s10461-008-9489-7
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy Among HIV-Infected Drug Users: A Meta-Analysis

Abstract: We conducted a meta-analysis of studies assessing adherence to highly active antiretroviral therapy (HAART) and a qualitative systematic review of factors associated with better HAART outcomes among HIV+ drug users (DU). Thirty-eight studies were considered, which analyzed 14,960 patients (11,394 HIV+ DU, 76.2%). Overall adherence (pooled percent of DU classified as adherent in each study) was 0.60 (95% CI: 0.52-0.68), similar to levels identified by studies conducted with HIV+ patients who are not drug users.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
165
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(180 citation statements)
references
References 87 publications
11
165
1
2
Order By: Relevance
“…Results are also consistent with previous studies showing that substance use, depressive symptoms, and HIV stigma are associated with lower levels of adherence, and trust or satisfaction with the healthcare provider are associated with higher levels of adherence [7],[8],[180],[224]. These results should be encouraging to HIV care providers, as they suggest several avenues for intervention that could result in improved adherence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results are also consistent with previous studies showing that substance use, depressive symptoms, and HIV stigma are associated with lower levels of adherence, and trust or satisfaction with the healthcare provider are associated with higher levels of adherence [7],[8],[180],[224]. These results should be encouraging to HIV care providers, as they suggest several avenues for intervention that could result in improved adherence.…”
Section: Discussionsupporting
confidence: 90%
“…One systematic review provided a comprehensive assessment of predictors/correlates of adherence to ART, but did not aggregate findings into quantitative estimates of their effect on adherence [5]. A number of other reviews did aggregate findings into quantitative estimates, but focused only on patient-reported barriers and facilitators [1], sociodemographic factors [3], clinical, comorbid, and treatment-related factors [6] and depression [7], or investigated a particular patient population, such as drug users [8]. …”
Section: Introductionmentioning
confidence: 99%
“…In that study, positive experiences reported included receiving equal treatment, being valued as a partner in one's health, social support provision, and confidentiality assurances while negative experiences included awkward interactions, irrelevant questions, rude treatment, blame, pity, excessive or differential precautions, care refusal, unnecessary referrals, delayed treatment, poor support, and confidentiality breaches. Our current findings are also similar to findings from studies that have investigated health care provision to substance users more generally [6,[36][37][38] as well as studies looking at the interactions between health care providers and substance users with HIV specifically [18][19][20]27]. For example, previous research has shown that substance users have been refused services or prescriptions [6], that substance users have been provided with less information than others and have received poorer quality care [37], and that HIV diagnoses have been provided to substance users in a detached and unsympathetic manner [18].…”
Section: Discussionsupporting
confidence: 89%
“…Stigmatization in health care settings, in particular, has been found to be highly detrimental to the well-being of substance users with HIV [8,19]. In fact, anticipated or enacted stigmatizing reactions from health care professionals can inhibit both substance use dependence treatment and HIV care [8,20,21] through testing delays [22,23], treatment avoidance [19,24,25], late entry into care [24], non-disclosure of substance use and/or HIV status [19,21,26], and poor access to antiretroviral therapy [27], all of which also impede HIV prevention efforts [19,28]. It is therefore important to engage in efforts to reduce the stigmatization of substance users with HIV in health care settings, and to improve interactions between health care professionals and substance users with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…HAART has an achievement on reducing disease progression, but it is also related to collateral problems like resistance of antivirals, toxicity and dosing which are preventing successful treatment of HIV [8,[10][11][12][13][14][15][16][17][18][19]. These shortfalls of HAART drugs' combinations point out the need for new drugs.…”
Section: Human Immunodeficiency Virus (Hiv) Is a Member Of Lentivirusmentioning
confidence: 99%